2021
DOI: 10.2196/31274
|View full text |Cite
|
Sign up to set email alerts
|

Adherence With Online Therapy vs Face-to-Face Therapy and With Online Therapy vs Care as Usual: Secondary Analysis of Two Randomized Controlled Trials

Abstract: Background Adherence to internet-delivered interventions targeting mental health such as online psychotherapeutic aftercare is important for the intervention’s impact. High dropout rates limit the impact and generalizability of findings. Baseline differences may be putting patients at risk for dropping out, making comparisons between online with face-to-face (F2F) therapy and care as usual (CAU) necessary to examine. Objective This study investigated ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
3
15
0
1
Order By: Relevance
“…Even though the high drop-out rate might limit the generalizability of the current results, several other studies have encountered similar drop-out rates in studies performed with psychosomatic rehabilitation patients (e.g. Lippke et al, 2021). Further, the results obtained by the validation study, which assess the serial mediation model with imputed data for measurement timepoint two, mimic the results of the present study.…”
Section: Limitations and Suggestions For Further Researchsupporting
confidence: 83%
“…Even though the high drop-out rate might limit the generalizability of the current results, several other studies have encountered similar drop-out rates in studies performed with psychosomatic rehabilitation patients (e.g. Lippke et al, 2021). Further, the results obtained by the validation study, which assess the serial mediation model with imputed data for measurement timepoint two, mimic the results of the present study.…”
Section: Limitations and Suggestions For Further Researchsupporting
confidence: 83%
“…In addition, psychotherapy carried out through the application also limits the monitoring of compliance with the use of the application according to the recommended duration ( Bruhns et al, 2021 ; Young et al, 2022 ). The results of the Lippke et al study show that there is a relevance between the expected treatment results and participants’ adherence to the use of application ( Lippke et al, 2021 ). However, other researchers concluded that using moderate-frequency applications produces only a small additional benefit when compared to the use of lower frequencies ( Donkin et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…With due caution, it could be suggested that self‐guided eHealth interventions promote the user's autonomy, making it easier for them to incorporate the recommendations and exercises practised during the program once it finishes. As previously stated, the problem with self‐guided interventions is that high rates of attrition might be a consequence of their flexibility, which would hinder detecting those at risk for dropping out (Lippke et al, 2021). Some degree of guidance has been associated with better outcomes (Baumeister et al, 2014) and, thus, a mixed format, such as a self‐guided web‐based program that includes some occasional online guidance (e.g.…”
Section: Discussionmentioning
confidence: 99%